SOLPS-ITER modeling of Ar and N seeded discharges in ASDEX upgrade and ITER. (March 2023) - Senichenkov, I.Yu.; Poletaeva, A.G.; Kaveeva, E.G.; Veselova, I.Yu.; Rozhansky, V.A.; Coster, D.; Bonnin, X.; Pitts, R.A.
Abstract: In this paper SOLPS-ITER simulations of Ar and N seeded discharges are presented for H-mode conditions on ASDEX Upgrade and for burning plasmas on ITER. These discharges are additionally compared with Ne seeded cases for both tokamaks. It is demonstrated that Ar and N are retained in the divertor, and that the amount of seeded impurity (measured both by the seeding rate in atoms/s and the averaged separatrix density) necessary to achieve the same divertor conditions is lower for Ar than for N. This is attributed to almost the same values of first ionization potential of Ar and N (if compared to e.g. Ne) and to higher Ar radiation efficiency. If the radiated power fraction within the numerical simulation grid is of the order of 50%, which is sufficient to achieve partial detachment at the outer target in both devices, radiation losses from the confined region remain small for Ar seeded ITER cases (about 6% of power from the outer core region included in the SOLPS-ITER computational domain with total volume 135 m 3 ). The fuel dilution by Ar remains lower than that by N and Ne, which corresponds to an Ar averaged separatrix concentration of 0.4%. From the point of view of target power handling, the boundary simulations thus demonstrate that Ar may be a suitable alternative seed impurity on ITER.